EFEKTIVITAS MODEL KOOPERATIF TIPE ROTATING TRIO EXCHANGE DALAM PEMBELAJARAN LOGARITMA - Nurhusain, Muhammad (Journal of Honai Math, 2021)
The mathematics students should construct their own mathematical concepts. The rotating trio exchange model of cooperative learning enables students to construct mathematical concepts. The purpose of this study is to determine the effectiveness of the rotating-trio-exchange cooperative learning model in the learning of mathematics, particularly logarithmic material. This research is a pre-experimental study using a pretest-posttest-only group design. The population of this study was students of class X SMA. The sample consisted of 21 students from class XB SMA YP-PGRI 3 Makassar. Data collection occurred twice, before and after the implementation of teaching and learning. The data were analyzed both descriptively and inferentially. The findings indicated that rotating group members during each discussion session while constructing mathematical concepts could elicit student activity, resulting in more meaningful learning and improved learning outcomes. Thus, the rotating trio exchange cooperative learning model is effective for learning logarithmic.